Investigation of rib's height effect on heat transfer and flow parameters of laminar water-Al2O3 nanofluid in a rib-microchannel - Akbari, O.A.; Toghraie, A.; Karimipour, A.; Safaei, M.R.; Goodarzi, M.; Alipour, H.; Dahari, M. (Elsevier, 2016)
The laminar forced convection heat transfer of water-Al2O3 nanofluids through a horizontal rib-microchannel was studied. The middle section of the down wall of microchannel was at a lower temperature compared to the entrance fluid. Simulations were performed for Reynolds numbers 10 and 100 and nanoparticle volume fractions of 0.00 to 0.04, inside a two-dimensional rectangular microchannel with 2.5 mm length and 25 μm width. The two-dimensional governing equations were discretized using a finite volume method. The effects of rib's hight and position, nanoparticle concentration and Reynolds number on the thermal and hydraulics behavior of nanofluid flow were investigated. The results were portrayed in terms of velocity, temperature and Nusselt number profiles as well as streamlines and isotherm contours. The model predictions were found to be in good agreements with those from previous studies. The results indicate that the normal internal ribs or turbulators, can significantly enhance the convective heat transfer within a microchannel. However, the added high ribs can cause a larger friction factor, compared to that in the corresponding microchannel with a constant height of the ribs. The results also illustrate that by increasing the rib's heights and volume fraction of nanoparticles, friction coefficient, heat transfer rate and average Nusselt number of the ribbed-microchannels tend to augment. In addition, the simulation results confirm that changing the solid volume fraction and the rib's height, cause significant changes in temperature and dimensionless velocity along the centerline of the flow, through the ribbed areas.